The Philosophy of Village Toponymy in Syamtalira Aron District, North Aceh Regency - Azhari; Rahmatillah; T. Muntazar (Indonesian Journal of Education and Social Humanities, 2026)
This study aims to describe the philosophical basis of village toponymy in Syamtalira Aron Sub-district, North Aceh Regency, and to categorize the toponymic aspects of village naming in the area. The research employs a qualitative approach with a descriptive qualitative method. The data consist of 34 villages in Syamtalira Aron Sub-district, and the data sources are indigenous residents who serve as informants, including traditional figures, elders, and youth who understand the local culture. Data collection was conducted through observation and in-depth interviews. Data analysis involved three stages: data categorization, data presentation, and conclusion drawing. The findings indicate that the community names their villages by observing their surrounding environment; if a particular type of tree or fruit is abundant in an area, its name is adopted as the village name. Overall, 23 villages fall under the aspect of manifestation (encompassing water features, topographic elements, and natural environment features), 5 villages under the social aspect, 3 villages under the cultural aspect, and 3 villages exhibit a mixture of toponymic aspects covering both social and manifestation elements. This research contributes to the documentation and preservation of local identity and cultural heritage from linguistic and historical perspectives.